Abundance of Eurasian lynx in the mountain taiga of the Southern Urals - Kiseleva, Natalia V. (Вестник Томского государственного университета. Биология)
The study aims to analyze the dynamics of the Eurasian lynx in the mountain taiga, and to search for the factors affecting the numbers of this predator. The study was conducted in the Southern Urals (Russia) from 2008 to 2019. The dynamics of lynx and its main prey numbers Capreolus pygargus, Lepus timidus and L. europaeus, Tetrao urogallus and Bonasa bonasia is based on the data obtained during the complex winter census (CWC). Annual CWCs were performed in Chelyabinsk Oblast with total area of 23.445.5 km². The hypotheses on the influence of snow depth on the number of lynx and the relationship between the dynamics of the predator and prey abundances were tested using regression method. The relationship between the number of lynx and snow depth were obtained using Spearman's coefficient. The number of lynxes varied from 51 to 281 individuals, population density - from 0.09 lynx/100 km2 to 0.48 lynx/100 km2. The lowest abundances were recorded in 2013 and 2016. In the winters of 2013 and 2016, the snow depth was 2.0-2.5 times greater than on average for long-term observations. However, no significant decrease in the number of the Siberian roe deer was observed in these years, while the number of lynxes decreased by 2 times compared to the previous years. No significant correlation was found between the abundance of lynxes and the Siberian roe deer, r = 0.25 ± 0.3. A negative relationship was found between the amount of precipitation and the winter number of lynxes (r = -0.717 ± 0.22; p ˂ 0.05). The amount of snow cover in the Southern Ural Mountains is an important factor affecting the distribution of ungulates. The snow depth may determine the lynx presence both directly and through the changes in the number of its main prey.